KEANEKARAGAMAN, PERSEBARAN, DAN POTENSI JENIS-JENIS Garcinia DI INDONESIA - Tahan Uji (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Indonesia has a high species richness of Garcinia (Garcinia spp.) and it is as a important basic materials for breeding of mangosteen (Garcinia mangostana). Based on examination of herbarium collections and literature study, there are 64 species of Garcinia encountered in Indonesia. Twenty-five of which occur in Kalimantan, 22 species in Sumatera and Sulawesi respectively, 17 species in Moluccas and Papua respectively, 8 species in Java, and 5 species in Lesser Sunda Island. Six species of those are as cultivation plants (Garcinia atroviridis, G. beccari, G. dulcis, G. mangostana, G. nigrolineata and G. parviflora), 58 species as the wild plants, 22 species as edible fruits, and 21 species as timber plants. Some members of Garcinia, e.i. G. malaccensis, G. picrorhiza and G. beccari are reported as rootstock potential species to be wedge-grafting by mangosteen (G. mangostana) seedlings.